Sindh Public Expenditure Review - World Bank Group (World Bank, Washington, DC, 2018)
Sindh has the potential to become a high middle-income province in Pakistan, but it lags far behind in terms of economic, social and development indicators. Sindh is also the most industrialized province, resource-rich and endowed with the country’s largest natural gas and coal reserves. In sum, it has the potential to become a high-growth and high-income region. Nonetheless, Sindh has yet to translate this potential into commensurate economic and social development. The province faces major developmental challenges. Sindh’s weak social indicators are partly the result of the inadequate reach and low quality of public service delivery. This Public Expenditure Review focuses on provincial finances and their utilization with the objective of identifying possible reforms to expand the resource envelope and ensure better value for money by improving the management and efficiency of public spending. It includes two important components: (i) a detailed analysis of the major revenue challenges and the various expenditures, including development spending and; (ii) and in-depth assessment of how some of the key government priorities are undertaken, such as education, health, and social protection. The hope is that by better understanding the constraints, reforms can be designed and implemented to maximize Sindh’s potential and promote a more equitable and productive path.